Análisis de los Censos Agropecuarios brasileños de los años de 2006 y 2017 para identificación de características de la población agrícola: Analysis of brazilian Agricultural Census of the years of 2006 and 2017 for identification of characteristics of the agricultural population - Arrais, Sayonara Chagas da Silva (2019)
Agriculture is a sector of the economy that is constantly developing and has been contributing considerably to the growth of Brazilian GDP. Due to the relevance of this segment, it is necessary to know the profile of rural workers who are contributing to these results. Thus, the research was conducted in order to identify the characteristics of the Brazilian agricultural population, from a comparative analysis performed with the data available in the Agricultural Census of 2006 and 2017. The study was developed through the selection of variables that presented data collected and disseminated during the two census periods, namely: legal status of the land, person who directs the property, relationship of farmers with financing, and division of establishments by region. As a result it was found that most producers own the land on which they work and most establishments are run by men. Relationships with financial institutions usually take place through bank branches and are intended to fund operations. The Northeast region is home to the largest number of rural establishments, with a large number of small properties and the opposite happens in the Midwest region, which has a large area of arable land distributed among few rural properties.